The impact of implementing professional ethics standards on job performance and professional behavior of employees in information institutions in Khartoum State: An analytical study - Osman, Ehlam Hussein Elsadig; Hafeez, Gadaa Taha Abdal; Mohammed, Abeer Taha Abdelhafeez (Edelweiss Applied Science and Technology, 2025)
This study aimed to assess the extent to which employees in information institutions in Khartoum State adhere to professional ethics standards from their perspective. It also aimed to evaluate their job performance and professional behavior. The study used a descriptive-analytical approach, with the research population consisting of employees in Khartoum State information institutions. The researchers selected 209 employees randomly. To measure the extent of adherence to professional ethics standards and their effect on job performance and professional behavior, the researchers used a custom-designed questionnaire. The study found that 91% of the sample reported that information institutions in Khartoum State meet the standard of responsibility toward society and beneficiaries. Employees also adhere to professional ethics, which positively affects their job performance and professional behavior. Key recommendations include that institutions should incorporate professional ethics standards into their internal policies and regulations to ensure that ethics are embedded in all institutional processes and job evaluations.